Soluble B-cell maturation antigen as a serum marker of MRD in patients with multiple myeloma - Dean, Erin A.; Li, Derek M.; Lin, Tuo; Sampson, Edith M.; Seifert, Robert P.; Hsu, Jack W.; Hiemenz, John W.; Wingard, John R. (Frontiers in Oncology, 2025)
IntroductionSerum soluble B-cell maturation antigen (sBCMA) has been shown to correspond to high disease burden in uncontrolled Multiple Myeloma (MM). However, it has not been extensively evaluated as a biomarker of minimal/measurable residual disease (MRD). MethodsIn this prospective observational correlative study, the primary objective was to correlate serum sBCMA with tumor burden in the bone marrow (BM) of patients with MM evaluated for first or salvage autologous stem cell transplantation. Paired samples were collected from 44 patients. BM overt disease was identified on morphological analysis or by standard flow cytometry (limit of detection (LOD) of 10-1). BM MRD was assessed by MRD flow cytometry (sensitivity of 1 aberrant clonal plasma cell in 105 nucleated cells) and/or next-generation sequencing (LOD of 10-6). ResultsFor transplant recipients (n= 36), the mean serum sBCMA (standard deviation (SD)) was 18.1 (11.7) ng/mL, BM overt disease was present in 12 (33.3%) patients and MRD only/No MRD in 20 (55.6%) patients. For non-transplanted patients (n= 8), the mean serum sBCMA was 9.7 (5.2) ng/mL, BM overt disease was present in 1 (12.5%) patient, while MRD only/No MRD in 5 (62.5%) patients. Serum sBCMA was associated with overt disease (p < 0.001), as well as MRD only/No MRD (p= 0.002). On multivariable logistic regressions modeling, higher serum sBCMA indicated higher odds of BM overt disease (odds ratio (OR) = 1.12, p = 0.007) and lower odds of MRD only/No MRD (OR = 0.91, p = 0.03). ConclusionSerum sBCMA was associated not only with BM overt disease, but also with BM detectable or below LOD MRD.